Validation of Nepali Version of Depression, Anxiety and Stress Scales (N-DASS21) among Higher Secondary School Students - Choulagai, Bishnu P; Sharma, Poojan; Sharma, Chandrakala; Neupane, Subas; Rana, Mita (Journal of Institute of Medicine Nepal, 2022)
Introduction Depression and anxiety are recognized as serious public health problems and are globally leading causes of disability in terms of total years lost due to disability. Depressive disorders often start at a young age; they reduce people’s functioning and are frequently recurring. The aim of this study was to examine the reliability and validity of Nepali version of Depression, Anxiety and Stress Scales (N-DASS21). Methods The study was conducted during February – May 2017 among higher secondary school students from nine public schools in Kathmandu. The sample size achieved for this study was 1007, with a response rate of 94.8%. The Nepali version of the questionnaire was used for data collection. Data were analyzed for validity using confirmatory factor analysis. Results The internal consistency of the three subscales for the constructs was assessed using Cronbach’s alpha with values obtained between 0.76 and 0.81 indicating a reliable scale. The receiver operating characteristic curves showed the area under the curve for depression and anxiety scales as 0.80 and 0.91, respectively. This indicates that the scales are accurate. Conclusions The Nepali version of DASS21 (N-DASS21) is psychometrically sound with good reliability and validity. It can be utilized as an instrument for measuring depression, anxiety, and stress in Nepali population.